2020
DOI: 10.1111/ppc.12497
|View full text |Cite
|
Sign up to set email alerts
|

The effect of computer game playing habits of university students on their sleep states

Abstract: Objective: The aim of this study is to evaluate the effect of computer game playing habits of university students on their sleep states. Design and Methods: The study was conducted cross-sectionally with the online survey method. Finding: In this study, it was determined that the students who played games for an average of ≥2 hours per day had later bedtime and later wake-up time, poorer sleep quality, and higher daytime sleepiness. It was found that as the level of game addiction increased, sleep quality decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
(55 reference statements)
0
18
0
Order By: Relevance
“…Prevalence rates of problematic gaming varied widely in the samples ranging from 1.2 to 73.9% (weighted mean = 16.0%), while three studies had comparison groups of similar sample size ( 41 , 71 , 76 ). The majority of samples ( n = 18) were recruited from primary- / high schools, while eight samples were recruited from college/universities ( 41 , 53 – 55 , 66 , 75 , 76 , 80 ), three were recruited from gaming communities ( 24 , 52 , 74 ), one was recruited from two pediatric lipid and obesity treatment clinics ( 77 ), one was recruited through social media ( 61 ), one was recruited in “non-working contexts” [e.g., pubs, sports associations, recreational places; ( 59 )], and two samples were recruited using random population sampling ( 56 , 79 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence rates of problematic gaming varied widely in the samples ranging from 1.2 to 73.9% (weighted mean = 16.0%), while three studies had comparison groups of similar sample size ( 41 , 71 , 76 ). The majority of samples ( n = 18) were recruited from primary- / high schools, while eight samples were recruited from college/universities ( 41 , 53 – 55 , 66 , 75 , 76 , 80 ), three were recruited from gaming communities ( 24 , 52 , 74 ), one was recruited from two pediatric lipid and obesity treatment clinics ( 77 ), one was recruited through social media ( 61 ), one was recruited in “non-working contexts” [e.g., pubs, sports associations, recreational places; ( 59 )], and two samples were recruited using random population sampling ( 56 , 79 ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies ( n = 32) investigated sleep using self-report questionnaires, while one study objectively measured sleep duration by employing Fitbit -actigraphy to register rest/activity cycles ( 77 ). Regarding self-report measures, 17 studies employed standardized sleep measurements where the most used instrument was the PSQI ( n = 8), while five studies employed assessments for insomnia ( 40 , 56 , 60 , 74 , 81 ), and two studies assessed for daytime sleepiness ( 53 , 70 ). The remaining studies assessed sleep-related outcomes using single/own-created items (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…That is, the longer you play online games, the less likely you are to fall asleep. Akçay and Akçay ( 2020 ) found that as levels of game addiction increased, individuals experienced decreased sleep quality, increased severity of daytime sleepiness, and delayed waking times. The above reflects the impact of Problematic internet use (PIU)on sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…The study characteristics are summarized in Table 2. Ten of the included twelve studies employed an observational study design (King and Delfabbro, 2009;Achab et al, 2011;Mario et al, 2014;Exelmans and Van den Bulck, 2015;Altintas et al, 2019;Evren et al, 2019;Akçay and Akçay, 2020;Ko et al, 2020;Rudolf et al, 2020;Wong et al, 2020), one study was a randomized crossover trial (Thomas et al, 2019) and another was a prospective cohort study (Thomée et al, 2015). All observational studies employed an online or paper-based survey approach, apart from two studies that also included face-to-face interviews (Exelmans and Van den Bulck, 2015;Ko et al, 2020), and one study that also performed clinical measurements in a controlled setting (Mario et al, 2014).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Sample sizes of the included studies ranged from 9 to 1066 participants, with cohorts spanning over ten countries. Overall, the sex distribution of the studies was biased toward males and included: two studies with all-male populations (Mario et al, 2014;Thomas et al, 2019), six studies with populations that were majority male (range: 77 to 98% male) (King and Delfabbro, 2009;Achab et al, 2011;Thomée et al, 2015;Altintas et al, 2019;Ko et al, 2020;Rudolf et al, 2020) and four studies with populations that were majority female (range: 56 to 71%) (Exelmans and Van den Bulck, 2015;Evren et al, 2019;Akçay and Akçay, 2020;Wong et al, 2020). The cohorts used in six of the studies comprised gamers from the general population (King and Delfabbro, 2009;Achab et al, 2011;Exelmans and Van den Bulck, 2015;Thomée et al, 2015;Altintas et al, 2019;Rudolf et al, 2020) and one study cohort comprised an elite team of League of Legends esports players (Thomas et al, 2019).…”
Section: Study Characteristicsmentioning
confidence: 99%